Beyond global rankings: Benchmarking public food procurement - Ana Miranda; Israel Klug (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Public food procurement (PFP) is commonly used by governments to advance social, economic and environmental goals. In many developing countries, it is intended to strengthen rural livelihoods and promote food security and better nutrition among vulnerable populations. This Working Paper presents the PFP Benchmarking methodology, an effective evaluation tool to assist governments to achieve these outcomes. The authors argue that PFP Benchmarking is a novel approach that favours participation, reflection and learning over global rankings, overcoming several criticisms of international benchmarking methodologies.
Keywords: 330; Local food procurement; sustainable public procurement; Home Grown School Meals; school feeding; food assistance procurement